Plant resistance to parasitic nematodes (CABI, 2002)
This book describes methods for evaluating the resistance and tolerance of plant cultivars to important parasitic nematode species, such as root-knot, cyst and reniform, and discusses the concepts and consequences of resistance. This book provides an invaluable source of information to all plant pathologists, nematologists and plant breeders.